Trends in Length of Hospice Care From 1996 to 2007 and the Factors Associated With Length of Hospice Care in 2007: Findings From the National Home and Hospice Care Surveys. (June 2014) - Sengupta, Manisha; Park-Lee, Eunice; Valverde, Roberto; Caffrey, Christine; Jones, Adrienne
Using the National Home and Hospice Care Surveys, we examined trends in length of hospice care from 1996 to 2007 and the factors associated with length of care in 2007. Results suggest that the increasing average lengths of care over time reflect the increase in the longest duration of care. For-profit ownership is associated with hospice care received for over a year.